Extended release matrix tablets of Stavudine: Formulation and in vitro evaluation - Saravanakumar, M; Venkateswaramurthy, N; Dhachinamoorthi, D; Perumal, P (Asian Journal of Pharmaceutics (AJP), 2014)
During the past two decades, there has been a steady increase in both the number of antiretroviral medications and the number of possible regimens available to manage human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS). But still, regimen fails due to some reasons such as toxicity, adverse effects, and consequent difficulties with patient adherence. Stavudine is the Food and Drug Administration approved drug for clinical use for the treatment of HIV infection, AIDS, and AIDS related conditions, either alone or in combination with other antiviral agents. The side effects of Stavudine are dose dependent and a reduction of the total administered dose reduces the severity of the toxicity. To reduce the frequency of administration and to improve patient compliance, a once daily sustained release formulation of Stavudine is desirable. Hence, in the present work, an attempt has been made to develop once daily sustained release matrix tablets of Stavudine using putative hydrophilic matrix materials such as hydroxyl propyl methyl cellulose (HPMC) K4M and Carbopol 974P.The prepared extended release tablets were then evaluated for various physical tests like diameter, thickness, weight variation, hardness, friability, and drug content uniformity.The results of all these tests were found to be satisfactory. Formulation F9 extended the drug release till the end of 24 hours and showed higher r values for zero order plot, indicating that drug release followed zero order kinetics. This finding reveals that above a particular concentration, HPMC K4M and Carbopol 974P are capable of providing almost zero order drug release.